علاقة الذكاء الجسمي الحركي بالتصرف الخططي الهجومي الفردي لدى لاعبي كرة السلة U19 - بلغول, كوثر ((institut d’éducation sportive et physique / Université de Mostaganem, 2023, 2023)
اﻟﻤﻠﺨص ﺒﺎﻟﻠﻐﺔ اﻟﻌرﺒﻴﺔ: ﻋﻨوان اﻟد ارﺴﺔ: ﻋﻼﻗﺔ اﻟذﻛﺎء اﻟﺠﺴﻤﻲ اﻟﺤرﻛﻲ ﺒﺎﻟﺘﺼرف اﻟﺨططﻲ اﻟﻬﺠوﻤﻲ اﻟﻔردي ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ U19 . ﻫدﻓت اﻟد ارﺴﺔ إﻟﻰ اﻟﺘﻌرف ﻋﻠﻰ ﻤﺴﺘوى اﻟذﻛﺎء اﻟﺠﺴﻤﻲ اﻟﺤرﻛﻲ ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ و ﻗﻴﺎس ﻤﺴﺘوى اﻟﺘﺼرف اﻟﺨططﻲ اﻟﻬﺠوﻤﻲ ﻟدﻴﻬم ٬ ﺒﺎﻹﻀﺎﻓﺔ إﻟﻰ اﻟﺘﻌرف ﻋﻠﻰ ﻨوﻋﻴﺔ اﻟﻌﻼﻗﺔ ﺒﻴن اﻟذﻛﺎء اﻟﺠﺴدي اﻟﺤرﻛﻲ و اﻟﺘﺼرف اﻟﺨططﻲ ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ ٬ ﺘﻤﺜﻝ اﻟﻔرض ﻤن اﻟد ارﺴﺔ ﻓﻲ وﺠود ﻋﻼﻗﺔ ﺒﻴن اﻟذﻛﺎء اﻟﺠﺴدي اﻟﺤرﻛﻲ و اﻟﺘﺼرف اﻟﺨططﻲ اﻟﻬﺠوﻤﻲ اﻟﻔردي ﻟدى ﻻﻋﺒﻲ ﻛرة ﺴﻠﺔ. ﺘم إﺨﺘﻴﺎر اﻟﻌﻴﻨﺔ ﺒﺎﻟطرﻴﻘﺔ اﻟﻌﺸواﺌﻴﺔ اﻟﻌﻤدﻴﺔ ٬ وﺒﻠﻎ ﺤﺠﻤﻬﺎ (23) ﻻﻋب ﻛرة اﻟﺴﻠﺔ دون 19 ﺴﻨﺔ ﻤن اﻟﺠﻤﻌﻴﺔ اﻷوﻟﻤﺒﻴﺔ آﻓﺎق ﻤﺴﺘﻐﺎﻨم ٬ واﻵداة اﻟﻤﺴﺘﺨدﻤﺔ ﻓﻲ ﻫذﻩ اﻟد ارﺴﺔ ﻫﻲ ﻤﻘﻴﺎﺴﻲ اﻟذﻛﺎء اﻟﺠﺴﻤﻲ اﻟﺤرﻛﻲ و اﻟﺘﺼرف اﻟﺨططﻲ اﻟﻬﺠوﻤﻲ اﻟﻔردي ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ ٬ وﻤن أﻫم اﻹﺴﺘﻨﺘﺎﺠﺎت اﻟﺘﻲ ﺘوﺼﻠت إﻟﻴﻬﺎ اﻟطﺎﻟﺒﺔ وﺠود ﻤﺴﺘوى ﻤن اﻟذﻛﺎء اﻟﺠﺴﻤﻲ اﻟﺤرﻛﻲ و وﺠود ﻋﻼﻗﺔ إﻴﺠﺎﺒﻴﺔ طردﻴﺔ ﺒﻴﻨﻪ وﺒﻴن اﻟﺘﺼرف اﻟﺨططﻲ ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ u19 و وﻤن أﻫم اﻹاﻗﺘ ارﺤﺎت اﻟﺘﻲ ﺘﻘﺘرﺤﻬﺎ اﻟطﺎﻟﺒﺔ اﻟﺒﺎﺤﺜﺔ ﻤﺴﺘﻘﺒﻼ ﻤﺤﺎوﻟﺔ إﻴﺠﺎد وﺘطوﻴر وﺴﺎﺌﻝ ﺤدﻴﺜﺔ ﻟﻘﻴﺎس ﻛﻝ اﻟذﻛﺎءات اﻟﻤﺘﻌددة و ﺨﺎﺼﺔ اﻟذﻛﺎء اﻟﺠﺴﻤﻲ اﻟﺤرﻛﻲ وﻤﺤﺎوﻟﺔ ﻗﻴﺎس اﻟﺘﺼرف اﻟﺨططﻲ ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﺴﻠﺔ ﺒﺸﻛﻝ ﻋﻠﻤﻲ ودﻗﻴق وﺘوﻓﻴر وﺴﺎﺌﻝ ﺘﺠرﻴﺒﻴﺔ ﻟﻘﻴﺎﺴﻪ ﺘﺠﻨﺒﺎ ﻟﻠوﺴﺎﺌﻝ اﻟﺘﻘﻠﻴدﻴﺔ .   Title: The relationship of physical intelligence with individual offensive tactical behavior of U19 basketball players Abstract : The study aimed to identify the level of physical-kinetic intelligence of basketball players and measure the level of their offensive tactical behavior, in addition to identifying the quality of the relationship between physical-kinetic intelligence and tactical behavior of basketball players. The hypothesis of the study is that there is a relationship between physical-kinetic intelligence And the individual offensive tactical behavior of basketball players. The sample was selected in a deliberate random way, and its size was (23) basketball players under 19 years old from the Olympic Association Mostaganem, and the tool used in this study was the measures of physical intelligence and the individual offensive tactical behavior of basketball players, and one of the most important conclusions reached The researcher has a level of bodily-kinesthetic intelligence and the existence of a direct positive relationship between it and the tactical behavior of basketball players u19, and one of the most important suggestions proposed by the student researcher in the future is to try to find and develop modern methods to measure all multiple intelligences, especially physical-kinetic intelligence, and try to measure the tactical behavior of basketball players The basket in a scientific and accurate manner and the provision of experimental means to measure it in order to avoid traditional methods
MES-2023-4
Keywords: الذكاء الجسمي الحركي - التصرف الخططي الهجومي - الفردي - لاعبي كرة السلة